Group Counseling of Cognitive Restructuring and Murattal Al-Qur’an Relaxation Techniques to Alleviate Indonesian Muslim University Students’ Academic Anxiety: Does it Work Effectively? - Riza, Julianne Kamelia; Wiyono, Bambang Budi; Hambali, IM; Muslihati, M; Adhli Al Karni, Noer Illahyat (Universitas Negeri Padang, 2023)
The objective of the study is to investigate the effectiveness of cognitive restructuring with murattal al-Qur‘an relaxation technique in reducing Indonesian Muslim university students’ academic anxiety. The research was conducted on Indonesian Muslim university students at Sekolah Tinggi Ilmu Tarbiyah Al Urwatul Wutsqo (STIT-UW) Jombang. A Quasi Experimental with Nonequivalent Control Group Design was employed to assess the effectiveness of group counseling using cognitive restructuring and Murattal Al-Qur’an relaxation techniques in reducing students’ academic anxiety during thesis writing. The participants included 22 students with high levels of academic anxiety, divided into experimental and control groups. The instruments utilized were academic anxiety scales, worksheets, reflection journals, and a group counseling module. Statistical analysis using the Mann–Whitney U Test was applied to identify differences in scores between the two groups. The results indicated that group counseling incorporating Cognitive Restructuring and Murattal Al-Qur’an relaxation techniques effectively alleviated the level of students’ academic anxiety. Having a positive way of thinking and a better physical and psychological condition, the university students have succeeded in reducing their academic anxiety level, and will assume the thesis as a challenge instead of threat, and also will motivate them to work on it immediately and accomplish their study in time. In conclusion, this group counseling approach may be recommended for college counselors to assist STIT-UW Jombang students experiencing academic anxiety while working on their theses, and it can be used as a conceptual and empirical reference for the development of counseling in the future.